استخدام الأفلام الكرتونية في تدريس المفردات )دراسة تجريبية في المدرسة الابتدائية الحكومية 34 بيدي (: fa'aliyyatu tadrisi al-mufradati bistikhdami al-aflami al-kartuniyyati "dirasah tajribiyyah fi al-madrasati al-ibtidaiyyatu al hukumiyyati bidi" - Jefriadi ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2024)
Based on the observation of researcher at MIN 34 Pidie, the researcher saw that teachers at the school could not get the students’ attention and could not impress them during studying. Furthermore, teachers also refrain from applying interesting learning methods and media, so students are less eager to learn. The purpose of this study is to identify if the application of cartoons transportations effective to increase students’ ability. Also it is to identify the students’ response in learning mufradat using cartoons. The method used in this research is pre experimental with one group pretest and postest design. The researcher used tests and questionnaire for data collection. And as a sample of research, the researcher select the second grader consisting of 25 students. The researcher used percentage values and average values to analyze student’s response data and analyze T test to gain influence. The result of T test indicates that applying cartoons can increase students’ ability. And the qustionnaire result that students’ response to learning the vocabulary by applying cartoons are in high values. Thus, mufrodat learning by using cartoon films can be called effective.